Implementasi Masyarakat Ekonomi ASEAN terhadap Elemen Tenaga Kerja Terdidik di Indonesia - Vivi Regina Haryati; Marieska Lupikawaty; Yahya Yahya (Department of Development Economics, Universitas Sriwijaya, 2019)
AEC implementation, it was expected that economic growth in the ASEAN region will be evenly distributed and transformed into a world market. The main characteristics of AEC were five elements such as the free flow of goods, services, investment, capital, and educated labor. The purpose of this study was to determine the benefits of implementing ASEAN Economic Community (AEC) in the educated workforce in Indonesia. The data analysis technique was descriptive qualitative and the data source were used secondary data from national and international publication data such as Badan Pusat Statistik, International Labour Organization, and United Nations Development Programme. The results of this study indicate that the implementation of AEC has not provided benefits yet for the Indonesian state, especially in educated workforce. Some results from the analysis of other data also showed that AEC has not been able to provide benefits because in terms of the quantity of Indonesian educated workers before the implementation AEC were actually better than after the implementation AEC. The author also suggested that in the future the implementation of AEC can provide benefits for educated workers in Indonesia, namely Indonesia need to improve the quality of human resources through educations, as well as the role of universities in contributing to improve the quality of human resources supported by the government and industry.